Answer:
WZX=57
Step-by-step explanation:
90-33 = 57
You don't have to use the equation unless you want to check yourself.
Answer:
Step-by-step explanation:
Standard equation of a line with slope, m and y - intercept b is y = mx + b.
Clearly. for the second equation has a different coefficient for x.
a ) The coefficient for x , is the slope of the line.
Though the y - intercept for each equation is same = - 4.
For example :
Expression A = 2 , when x = 1
Expression B = 8 , when x = 1
Expression C = 2 , when x = 1
b) From above :
c) Expression A and C are equivalent because the coefficient of x
is the same for A and C.
Answer:
go a head what can i help you with
And Then Simplify it!
50 points!
Step 1: Simplify both sides of the equation.
5(−3x−2)−(x−3)=−4(4x+5)+13
5(−3x−2)+−1(x−3)=−4(4x+5)+13(Distribute the Negative Sign)
5(−3x−2)+−1x+(−1)(−3)=−4(4x+5)+13
5(−3x−2)+−x+3=−4(4x+5)+13
(5)(−3x)+(5)(−2)+−x+3=(−4)(4x)+(−4)(5)+13(Distribute)
−15x+−10+−x+3=−16x+−20+13
(−15x+−x)+(−10+3)=(−16x)+(−20+13)(Combine Like Terms)
−16x+−7=−16x+−7
−16x−7=−16x−7
Step 2: Add 16x to both sides.
−16x−7+16x=−16x−7+16x
−7=−7
Step 3: Add 7 to both sides.
−7+7=−7+7
0=0
Answer:
All real numbers; the simplification is described below.
Step-by-step explanation:
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13
Let's keep in mind PEMDAS (the order of operations) to simplify and solve this. First, we'll distribute inside each set of parenthesis!
5(-3x) + 5(-2) -1(x) -1(-3) = -4(4x) -4(5) + 13
See how we've taken the outer term on the outside of the parenthesis and multiplied it to each term inside the parenthesis. Simplify further.
-15x - 10 - x + 3 = -16x - 20 + 13
Now we can combine like terms! I will bold the terms I am combining.
-15x - 10 - x + 3 = -16x - 20 + 13 (combining the x terms on the left)
-16x - 10 + 3 = -16x - 20 + 13 (combining the constants on both sides)
-16x - 7 = -16x - 7
Aha! It looks like we have an equation that's literally equal to itself. If we were to simplify this, or put in any number, we'd get that number equals itself. For example:
-16(1) - 7 = -16(1) - 7
-16 - 7 = -16 - 7
-21 = -21
Any number you put in here will make the equation true, so these lines must be the same line. That means the solution is all real numbers.
The average rate of population change per year will be 2.2 million.
The difference in population will be:
= 324 million - 313 million.
= 11 million
The difference in years will be:
= 2017 - 2012
= 5 years.
The average rate of population change per year will be:
= 11 million / 5
= 2.2 million
Read related link on:
Answer: 2.2 million.
Step-by-step explanation:
To get the answer, you would need to make 324 million and 2017 a fraction(324 million as numerator (top), 2017 as denominator (bottom) and the same for 313 million and 2012) . From there, you subtract both fractions. You will get 11/5, which would equal 2 1/5. Multiply the 2 1/5 by 2 to get 2 20/100.
Answer:
Step-by-step explanation:
The problem tell us that is the inverse of , where:
So, we need to find the inverse function of in order to find
Let's find the inverse function using the following steps:
1. Replace with :
2. Solve the equation for :
3. Replace every with a and replace every with a :
4. Finally, replace with
Therefore:
Answer:
6 liters of cream.
2 liters of blue.
Step-by-step explanation:
We are given that To get the paint colour you want, you mix 2 parts red with 3 parts cream and 1 part blue.
Ratio is 2:3:1
Now we are given that we need to calculate how much cream and blue paint will you need to mix with 4 litres of red
Since we are mixing 2 parts of red and we have 4 litres
⇒2 times 2 = 4 litres
So, since they mix 3 parts of cream
Thus 3*2= 6 lites
So they use 6 liters of cream.
Since they mix 1 parts of blue
Thus 1*2= 2 liters
So, they use 2 liters of blue.